2017
DOI: 10.1037/adb0000286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of attentional retraining on cognition, craving, and smoking in African American smokers.

Abstract: African American cigarette smokers have lower rates of cessation than Whites and live in communities with a higher number of tobacco advertisements. Exposure to smoking cues may promote smoking and undermine cessation. It may be possible to reduce attention to smoking cues (“attentional bias”). In this study, we investigated the effect of Attentional re-training (AR) on attentional bias and smoking in African-American smokers. Non-treatment seeking African American smokers (N = 64) were randomly assigned to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 66 publications
1
37
1
Order By: Relevance
“…Five of the studies targeted automatic processes regarding alcoholism [ 19 , 20 , 31 , 32 , 35 ]. Two studies targeted smoking attitudes and behavior [ 35 , 40 ]. Two studies targeted automatic processes toward anxiety [ 21 , 39 ], and one study targeted automatic processing toward both anxiety and depression [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of the studies targeted automatic processes regarding alcoholism [ 19 , 20 , 31 , 32 , 35 ]. Two studies targeted smoking attitudes and behavior [ 35 , 40 ]. Two studies targeted automatic processes toward anxiety [ 21 , 39 ], and one study targeted automatic processing toward both anxiety and depression [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The type of digital technology most often used to execute the intervention was a personal computer or laptop via a website (n=8) [ 20 , 25 , 26 , 35 , 42 - 45 ], followed by the use of a smartphone app (n=5) [ 21 , 34 , 39 , 41 , 46 ]. One study was delivered on a personal digital assistant device [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The articles described mHealth apps for the delivery of attention or cognitive bias modification for following conditions: insomnia (n=1), social anxiety (n=1), anxiety disorder (n=3), alcohol use disorder (n=1), and tobacco use disorder (n=2). Table 1 [ 17 , 19 - 25 ] summarizes the main characteristics of the studies that we included. Nearly all of the trials used either the dot-probe or visual-probe task, except for 1 study that used cognitive bias for interpretation intervention, and another that did not specify the task applied.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the outcomes, 7 studies reported effectiveness and only 1 reported no effect. Bias modification was found to be effective, as it helped improve symptoms of insomnia and cognitive symptoms of presleep arousal [ 17 ]; reduce subjective anxiety [ 20 ]; improve performance on stress task [ 21 ]; reduce attentional biases for cigarettes [ 22 , 25 ]; reduce the amount of alcohol consumed [ 24 ]; and reduce prenatal stress and anxiety [ 23 ]. However, Yang et al [ 19 ] reported that bias modification was not effective, as the bias scores among participants with social anxiety disorders were not reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the published literature to date, there are several studies that have evaluated the potential and effectiveness of mHealth bias modification. Of the studies, seven reported that mHealth bias modification was effective for participants with a variety of disorders, namely insomnia, alcohol, tobacco use, or social anxiety disorders [ 12 - 18 ]. mHealth technologies are increasingly being harnessed for the delivery of bias modification, as mobile technologies allow for the training to be conducted in diverse locations, thus helping in the generalization of clinical benefits [ 19 ].…”
Section: Introductionmentioning
confidence: 99%